Primary Serological Status and Immunological Efficacy of Vaccination against Streptococcus Pneumoniae and Haemophilus Influenzae Type b in Children with Bronchopulmonary Dysplasia: a Cohort Study - Klavdiia A. Kazakova; S. Leyla Namazova-Baranova; Irina V. Davidova; Yrii S. Akoev; Marina V. Fedoseenko; Natalya E. Tkachenko; Elena G. Filyanskaya; Vasiliy N. Lubov (Педиатрическая фармакология)
Background. The primary serological status of children with bronchopulmonary dysplasia (BPD) with respect to respiratory significant pathogens remains unstudied. Wherein, the efficacy of vaccination of children with BPD against Streptococcus pneumoniae and Haemophilus influenzae type b (Hib) has been studied in a small number of studies which results are contradictory.Objective. Our aim was to study the pre-vaccinal serological status with regard to S. pneumoniae and Hib and the immunological efficacy of vaccination against these infections in children with BPD.Methods. The study included children with BPD without exacerbation. The immunological efficacy of conjugate vaccines — pneumococcal 13-valent and against Haemophilus influenza type b — was assessed by the level of IgG against S. pneumoniae and Hib using the ELISA method. The level of antibodies was determined before vaccination and 1 or 3–6 months afterwards.Results. The study included 32 children with BPD, mean age at the time of determining primary serological status was 13.3±1.3 months, at the time of vaccination — 15.2±1.5 months. The mean gestational age was 28.7±0.8 weeks, the body weight at birth was 1225±180 g. Before vaccination, all children with BPD had no protective antibody titre against S. pneumoniae and Hib averaging 0.2±0.034 and 0.13±0.0106 mg/L, respectively. One month after vaccination, the level of antibodies to S. pneumoniae reached 12.9±2.34 mg/L to Hib — 3.34±0.769 mg/L.Conclusion. After immunization with a pneumococcal 13-valent conjugate vaccine and a conjugate vaccine against Haemophilus influenzae type b, the concentration of IgG against S. pneumoniae exceeded the protective level in all examined patients (100%), the concentration to Hib — in 29 (90.6%).